Dynamics of perinuclear actin ring regulating nuclear morphology - Yang, Haoxiang; Sun, Houbo; Shen, Jinghao; Wu, Hao; Jiang, Hongyuan (Applied mathematics and mechanics, 2024)
Cells are capable of sensing and responding to the extracellular mechanical microenvironment via the actin skeleton. In vivo, tissues are frequently subject to mechanical forces, such as the rapid and significant shear flow encountered by vascular endothelial cells. However, the investigations about the transient response of intracellular actin networks under these intense external mechanical forces, their intrinsic mechanisms, and potential implications are very limited. Here, we observe that when cells are subject to the shear flow, an actin ring structure could be rapidly assembled at the periphery of the nucleus. To gain insights into the mechanism underlying this perinuclear actin ring assembly, we develop a computational model of actin dynamics. We demonstrate that this perinuclear actin ring assembly is triggered by the depolymerization of cortical actin, Arp2/3-dependent actin filament polymerization, and myosin-mediated actin network contraction. Furthermore, we discover that the compressive stress generated by the perinuclear actin ring could lead to a reduction in the nuclear spreading area, an increase in the nuclear height, and a decrease in the nuclear volume. The present model thus explains the mechanism of the perinuclear actin ring assembly under external mechanical forces and suggests that the spontaneous contraction of this actin structure can significantly impact nuclear morphology.